2023
DOI: 10.1111/dme.15066
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fear of hypoglycaemia on sleep in adolescents with type 1 diabetes

Abstract: Aims: Fear of hypoglycaemia (FOH) can contribute to impaired sleep for adults with type 1 diabetes (T1D) and parents of children with T1D, although it is unknown how FOH may affect sleep for adolescents with T1D. This study examines the relationship between adolescent FOH and sleep and assessed the influences of continuous glucose monitor (CGM) and insulin pump use. Methods: Adolescents ages 14-18 years with T1D completed questionnaires evaluating FOH (Child Hypoglycemia Fear Survey) and sleep (Pittsburgh Slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(89 reference statements)
1
2
0
Order By: Relevance
“…The results revealed a strong negative correlation between FoH and sleep quality after adjustments for numerous confounders. The findings of our study were consistent with those of the research conducted on an American adolescent population [ 39 ]. FoH places a major psychological burden on individuals with DM and can affect sleep quality [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results revealed a strong negative correlation between FoH and sleep quality after adjustments for numerous confounders. The findings of our study were consistent with those of the research conducted on an American adolescent population [ 39 ]. FoH places a major psychological burden on individuals with DM and can affect sleep quality [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…The authors found that, in 95 adolescents, the worry subscale of fear of hypoglycaemia was associated with sleep duration and that users of continuous glucose monitoring slept for longer. 4 Importantly, the use of continuous glucose monitoring and pumps, while improving some metrics of sleep, did not interact with the relationship between fear of hypoglycaemia and sleep. This underlines the message that technologies are an adjunct to support and education for fear of hypoglycaemia and, while they can reduce worry and help people to have better sleep, they do not fundamentally change the underlying fear.…”
mentioning
confidence: 96%
“…In this issue, the impact of fear of hypoglycaemia on sleep for adolescents with type 1 diabetes is described. The authors found that, in 95 adolescents, the worry subscale of fear of hypoglycaemia was associated with sleep duration and that users of continuous glucose monitoring slept for longer 4 . Importantly, the use of continuous glucose monitoring and pumps, while improving some metrics of sleep, did not interact with the relationship between fear of hypoglycaemia and sleep.…”
mentioning
confidence: 98%